Analytical Review on Graphical Formats Used in Image Steganographic Compression - Roshidi Din; Osman Ghazali; Alaa Jabbar Qasim (Institute of Advanced Engineering and Science, 2018)
This paper reviews the method of classification of the types of images used in data concealment based on the perspective of the researcher’s efforts in the past decade. Therefore, all papers were analyzed and classified according to time periods. The main objective of the study is to infer the best types of images that researchers have discussed and used, several reasons will be shown in this study, which started from 2006 to 2017, through this paper the pros and the cons in the use of favourite types in the concealment of data through previous studies.